A propriedade distributiva da multiplicação: uma visão diagnóstica do processo - DIAS, Josete Leal (2004)
The objective of this study is to investigate the application of the distributive property of multiplication in the numeric and algebaric contexts, and in the solution of problems carried out by students of Basic Education in a public school in Belém, examining in what measure the application of the distributive property is related to the difficulties found in the mathematics learning. In this investigation, we highlight the diagnostic evolutation and the error as a didactic strategy as well as hermeneutic contribution concerning the ways of assessing the process of acquiring the skills of math. The study inlued fifth and seventh grade students of basic course and the frist uear of high school, out of forty-five sibjects. The collection was carried out in two moments by applying a test presenting three sets of questions in a total of thirteen problem situations. The procedures of the subjects concerning the application of the distributive property were described in a perspective of qualitative analysis. The protocols presented were to look for behavior patterns in the understanding of the subjects on the distributive property, as well as to clarify situations which were entitled didactic obstacles. As a result, it was evident that the students presented some difficulty to work with the application of distributive property when the latest one is found in the context of problem solutions, as well as contents like algebraic sum, study of variables, nonsimilarterms are not in the domain of most of the students.